The determinants of share prices performance of insurance companies listed in the Pakistan stock exchange (psx) - Khan, Ali Burhan (2020)
This study examines the determinants of share prices performance of all listed insurance companies in Pakistan Stock Exchange (PSX) from year 2009 to 2016. The insurance companies generate indispensable contributions towards an economic system. However, in the case of insurance companies in the PSX, the insurers have been experiencing a decline in their share prices performance. Subsequently, a significant number of insurance companies are delisted from PSX. Therefore, this study aimed to identify the macroeconomic factors (inflation, interest rate, money supply, exchange rate and market return) and firm-specific factors (leverage, liquidity, firm size, profitability, firm age, market share, dividend payout behaviour and firm efficiency) that affect the share prices performance of insurance companies of PSX. This study also contributes to the existing literature by analyzing the moderating impact of firm efficiency on the relationship between firm-specific variables and insurance companies’ share prices. The empirical analysis encompasses 22 listed insurance companies in PSX from 2009 to 2016 via multiple regression analyses. The results highlight that market return is the only significant macro-economic variable that affects share prices performance. Meanwhile, the analysis also identifies leverage, firm size, profitability, firm age, market share and firm efficiency as the significant firm-specific variables to influence share prices performance. Firm efficiency is a crucial success factor in any organizations. Thus, the management of insurance companies should ensure efficiency in their operations to improve share prices performance. Based on the results, firm efficiency is indeed a significant variable that can moderates the relationship between insurance companies’ size and their share prices. In a nutshell, the findings from this study implied that overall share prices performance of insurance companies in PSX is mostly-affected by firm-specific factors instead of macroeconomic ones.